PENGARUH VOLUME PERDAGANGAN SAHAM, FREKUENSI PERDAGANGAN SAHAM, VOLATILITAS HARGA SAHAM, DAN KAPITALSIASI PASAR TERHADAP RETURN SAHAM PERUSAHAAN MAKANANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nasution, Latif Zubaidah; Sulistyo, Sulistyo; halim, abdul (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2016)
The purpose of this study was to examine and explain: 1) partial effect on the volume of shares trading on stock returns food and beverage companies listing on the Stock Exchange; 2) partial effect on the frequency of stock to return stock trading food and beverage companies listing on the Stock Exchange; 3) partial effect on stock price volatility on stock returns food and beverage companies listing on the Stock Exchange; 4) partial effect on the market capitalization of the stock return food and beverage companies listing on the Stock Exchange This type of research is explanatory research, which explains the causal relationship between research variables through hypothesis testing. The necessary data consisting of upper frequency stock trading, stock trading volume, volatility of stock price, market capitalization and stock return as many as 18 food and beverage companies during the years 2014 to 2015, was obtained from internet access to www.idx.co.id , Then analyzed using linear regression. Meanwhile, to test the hypothesis was tested by t-test. The results of this study prove that the first volume of stock trading is partially an effect on stock returns food and beverage companies listing on the Stock Exchange; The second frequency stock trading partially influence on stock returns food and beverage companies listing on the Stock Exchange; The third stock price volatility stock trading partially influence on stock returns food and beverage companies listing on the Stock Exchange; The fourth stock market capitalization partially influence on stock returns food and beverage companies listing on the Stock Exchange